2002
DOI: 10.1111/j.1572-0241.2002.05668.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of helicobacter pylori infection in the incidence and clinical course of monoclonal gammopathy of undetermined significance

Abstract: The results of our study give increased credibility to the theory that in a proportion of patients the pathogenesis of MGUS involves chronic antigenic stimulation and H. pylori is implicated. The search for H. pylori infection and an attempt to eradicate the bacterium in positive cases seem to be appropriate in patients diagnosed with MGUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…There was no clear association between radiation exposure and the disease progression of MGUS [10]. Furthermore, a previous study demonstrated that MGUS subjects had a high rate of Helicobacter pylori infection (68.4%) [11]. Epidemiological identification of the risk factors for MGUS may shed light on the pathogenesis of this monoclonal plasma cell disorder.…”
Section: Introductionmentioning
confidence: 95%
“…There was no clear association between radiation exposure and the disease progression of MGUS [10]. Furthermore, a previous study demonstrated that MGUS subjects had a high rate of Helicobacter pylori infection (68.4%) [11]. Epidemiological identification of the risk factors for MGUS may shed light on the pathogenesis of this monoclonal plasma cell disorder.…”
Section: Introductionmentioning
confidence: 95%
“…Infection by H. pylori has been linked to monoclonal gammopathy of undetermined significance (MGUS) [8]. Chronic antigenic stimulation and genetic susceptibility predispose to MGUS [9], which affects less than 5% of the population [10], and may precede multiple myeloma, plasma cell leukemia, or MALT lymphoma [11].…”
Section: Approximately Half Of the World's Population Is Infected Bymentioning
confidence: 99%
“…Resolution of the gammopathy is observed in up to 30% of cases by eradicating the bacteria [257], a relationship confirmed by some authors [246,258] but not by others [215,259].…”
Section: Plasma Cell Dyscrasiasmentioning
confidence: 85%